Utilization of Contraceptive Methods by Postpartum Patients at An-Nisaa' Hospital Blitar During the COVID-19 Pandemic - Mayda Sumantri, Yuriska; Handayani, Puspita (Rifa'Institute, 2023)
Introduction: The COVID-19 pandemic has had a significant impact on various aspects of health services, one of which is access to contraception. Objective: The people of Blitar Regency, in choosing the Long-Term Contraceptive Method, have preferences that refer to safe use, ease to use, effectiveness, and advantages over other methods. Method: This research is quantitative descriptive research. This research was conducted to describe the use of contraceptive methods in postpartum patients at An-Nisaa Hospital in 2020 and 2021. Data analysis used univariate or descriptive analysis by looking at the frequency distribution of each contraceptive method used. Result and Discussion: Generally, the percentage of acceptors for postpartum patients compared to the number of deliveries is still at the same percentage, namely 67.64% in 2020 and 69.4% in 2021. Conclusion: The result is that the intrauterine device (IUD) method of contraception was widely chosen by patients postpartum during 2020-2021, where in 2020 there were 91.66% of Family Planning acceptors, and in 2021 there were 92.23% of PROGRAM KELUARGA BERENCANA PASCA PERSALINAN acceptors chose intrauterine devices